Ecological Study Of Lokan Mussels (Geloina spp) In Mangrove Likupang Village, Ambong Village, North Minahasa - Isran Fairan Tanja; Gaspar D. Manu; Jety K. Rangan; John L. Tombokan; Jans Dj. Lalita; Ferdinand Frans Tilaar (Sam Ratulangi University, 2022)
Based on the observations of 48 individuals and 2 species, the results of analysis of the Density of Lokan Mussels (Geloina spp) at the 3 stations showed that the highest density was at station II of 6.8 Ind/m2 and followed by station III of 6.4 Ind/m2 and the lowest was at station I of 6 Ind/m2, with a total density of 19.2 ind/m2.Equation The long-weight relationship at station I of the Geloina erosa species is W = -2.0299 + 2.3331L with a value of b <3 meaning (negative allometric), the species of Geloina expansa is W = -4.5186 + 3.6111L with a value of b> 3 means (positive allometric). The long-weight relationship at station II of the Geloina erosa species is W = -7.9857 + 5.4459L with a value of b > 3 meaning (positive allometric), the species of Geloina expansa is W = -5.6998 + 4.2558L with a value of b > 3 means (positive allometric ). The long-weight relationship at station III of the Geloina erosa species was W = -4.8901 + 3.832L with a value of b > 3 meaning (positive allometric), Geloina expansa species was W = -4.4782 + 3.5928L with a value of b > 3 meaning (positive allometric). Keywords: ecological studies; Density, weight length relationships, dispersal patterns Abstrak Berdasarkan hasil pengamatan jumlah individu 48 dan terdapat 2 spesies, hasil analisisKepadatan Kerang Lokan (Geloina spp) pada ke 3 stasiun menunjukan kepadatan tertinggi terdapat pada stasiun II sebesar 6,8 Ind/m2 dan di ikuti stasiun III sebesar 6,4 Ind/m2 dan terendah pada stasiun I sebesar 6 Ind/m2 , dengan kepadatan total 19,2 ind/m2. Persamaan Hubungan panjang berat pada stasiun I spesies Geloina erosa adalah W = - 2,0299+2,3331L dengan nilai b < 3 artinya (allometrik negatif ), spesies Geloina expansa adalah W = - 4,5186 + 3,6111L dengan nilai b > 3 artinya (allometrik positif). Hubungan panjang berat pada stasiun II spesies Geloina erosa adalah W = - 7,9857 + 5,4459L dengan nilai b > 3 artinya (allometrik positif), spesies Geloina expansa adalah W = - 5,6998 + 4,2558L dengan nilai b > 3 artinya (allometrik positif ). Hubungan panjang berat pada stasiun III spesies Geloina erosa adalah W = - 4,8901 + 3,832L dengan nilai b > 3 artinya (allometrik positif), spesies Geloina expansa adalah W = - 4,4782 + 3,5928L dengan nilai b > 3 artinya ( allometrik positif). Kata kunci : studi ekologi ; Kepadatan, hubungan panjang berat, pola penyebaran